A Stylistic Analysis of Complexity in William Faulkner’s That Evening Sun - Israa Burhanuddin Abdurrahman; Hajir N. Turki; Ruqaiya Burhanuddin Abdurrahman; Ali Hussein Hazem; Zahraa Muharam Salman (At-tadzkir: Islamic Education Journal, 2026)
A stylistic analysis refers to the identification of the patterns of usage in writing. However, such an analysis is not restricted just to the description of the formal characteristics of texts, but it also tries to clarify their functional importance for the interpretation of the text. This paper tries to answer the question of how William Faulkner functions his complex style to convey meaning in That Evening Sun. It aims to check out William Faulkner's style and how he manages sentence structure and sentence length in establishing images and meaning in the text. This paper follows a mixed-methods research design. It analyzes the short story That Evening Sun according to Leech & Short's model (2007) to identify the syntactic complexity according to the different grammatical structures. The results of analysis show that Faulkner uses his complex styles as a means to convey meaning especially when it revolves around complex situations and complicated characters. The study demonstrates that teaching syntactic complexity through literary texts can enhance students' understanding of how grammatical structures serve narrative and thematic functions. It also validates Leech & Short's model (2007) as an effective framework for empirically linking stylistic choice to literary meaning in classroom contexts.